Understanding the blast damage mechanisms in slopes using observations and numerical modelling - Etchells, S.J.; Sellers, E.J.; Furtney, J. (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
Observations made in the field, together with numerical modelling using the Hybrid Stress Blast Model (HSBM) are presented to further understand the mechanisms contributing to blast damage in pit slopes. The aim being to examine the contributing variables such as the variability of the rock mass, blast design, charging technique and current wall control techniques in the industry. The HSBM blast modelling research tool, with some improvements to the near field logic, successfully demonstrates different techniques of wall control that are being used in the industry. It is shown how the orientation of the discontinuities relative to the pit walls can negatively affect the performance of both a presplit and a post -split if not taken into consideration in the blast design. Damage reduction in a presplit requires the correct spacing, decoupling ratio and split factor. Controlling the fractures at the end of a presplit becomes important if there is a need to reduce the number of holes per delay to control vibrations and air blast, because there is an accumulation of damage into the highwall at the end of each section. The use of post-splitting is more favourable in terms of reducing production time. Dynamic post-splits at a hard rock quarry are studied and show fair results for jointing at an acute angle to the face. Poor ground conditions result when the jointing is at an obtuse angle relative to the face. This technique should only be used if the risk on the operation is appropriately managed, and the mine is sufficiently shallow. An effective wall control technique relies on an effective trim blast. Observations highlight damage up to ten metres or more into the slope with poor blasting, if an ineffective wall control technique were to be applied. The numerical modelling confirms that the linear charge factor is the main contributing factor to damage, although it is closely related to the powder factor and cannot be considered in isolation. Limitation of confinement is the major link to limiting damage. By understanding blast damage mechanisms, pit slope stability risks can be better quantified and modelled. This will allow optimisation of a wall control technique to a specific rock mass, and to link the expected damage on a bench scale to the overall pit slope.